PENINGKATAN PEREKONOMIAN MASYARAKAT DI DESA PANDANBLOLE MELALUI PEMBERDAYAAN KESEJAHTERAAN KELUARGA - Mardi , Astutik; Rafka , Ardiantoro (COMVICE: Journal Of Community Service, 2024)
The potential of rural communities is natural resources through agriculture. This potential can be optimized by improving village human resources, especially in terms of how to process agricultural products so that they can be marketed effectively. However, this cannot be done alone. It requires assistance from various parties, one of which is from STIE PGRI Dewantara Jombang, one of the leading campuses in the city of Jombang. The Community Service activity carried out by the author's team focused on increasing the marketing reach of the fried onion business of Family Welfare Programme members of Pandanblole Village, Ploso, Jombang. This activity was carried out intensively for approximately one month, namely March 2024, assisted by students. The results of the activities were positive, including improving the appearance of fried onion product packaging and increasing turnover and marketing reach of Fried Onions in Pandanblole Village.